Biografía y vivencia global en el Río de la Plata durante una época de guerras y revoluciones, 1795-1815 - Ibarra, Antonio (El Colegio de México, A.C., 2023)
This article is based on the testimony of Juan de Latre y Aysa, an Aragonese sailor with great military experience and cartographic knowledge, who improved upon the British maps that were used by the Royal Company of the Philippines. A businessman, he sailed for the Company, profiting off of non-freight goods on the voyages to Rio de la Plata. His background, local roots and global experience made him a military actor at the edges of the Spanish Empire, his testimonies taking on importance for their reading of the world. The testimonies of his career are a combination of “factualities” and agency: records and testimonies of military service, navigation logs in his own hand, accounts by his fellow sailors, memorials, documented evidence of events and expressions of the subjectivities in play. Together, they have allowed us to unite fragments, not without seams, to reveal a life that oscillated between chance and necessity.